Théorie de la régulation : la perspective oubliée du développement - Noureddine El Aoufi (Revue de la Régulation)
First, the article tries to revisit the theory of regulation, given the framework of development and under-development. The examination of the research program over thirty years stresses the idea of a western-centered orientation of the recent works and a progressive tendency to a restriction of the field of analysis to the variety of canonic fordism, especially that of Western countries.This self-reference system is more than territorial insofar as it deals with an approach that gives substance to capitalism by looking inside its system for the fundamental laws, whereas peripheries are only ad hoc and over-determined configurations.Second, the development perspective is brought out as a constituent generality of capitalism that declines in specific trajectories of the sub-fordism variety. By performing the economical and merchant functioning onto developing economies, the symbolic activity, even in its archaic form, is reflexively linked to the rational component of the center- dominant capitalist dynamics.Eventually, the article pleads for a theoretical (especially as for Amartya Sen) and empirical re-equipment of the theory of regulation extended to the under-development process.This orientation could aim, not only an improvement of the analysis and a criticism of the theory of regulation, but the institution of a normative consistency upon pragmatic reforms that combine human development and regulation inside developing countries.